2003
DOI: 10.1093/carcin/bgg063
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in the proliferative response of mouse hepatocytes to treatment with the CAR ligand, TCPOBOP

Abstract: The nuclear receptor Constitutive Androstane Receptor (CAR) binds DNA as a heterodimer with the retinoic-X receptor and activates gene transcription. Previously, in vitro studies have shown that the testosterone metabolites, androstenol and androstenol, inhibit the constitutive transcriptional activity of CAR, suggesting that differences might exist in the response to CAR-mediated gene activation between different sexes. In this study, we have analyzed the response of female and male CD-1 mice to stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…It was previously shown that the basal expression of CAR is higher in female than male mice (Kawamoto et al, 2000). Furthermore, the CAR activator (TCPOBOP) resulted in higher induction of the mRNA expression of Cyp2B10 (CAR target gene) in female than male rats (Ledda-Columbano et al, 2003). This might explain the finding in this article that CAR activators do not appear to be strong inducers of Sults, especially in male mice, but are better inducers of Sults in female mice.…”
Section: Discussionmentioning
confidence: 53%
“…It was previously shown that the basal expression of CAR is higher in female than male mice (Kawamoto et al, 2000). Furthermore, the CAR activator (TCPOBOP) resulted in higher induction of the mRNA expression of Cyp2B10 (CAR target gene) in female than male rats (Ledda-Columbano et al, 2003). This might explain the finding in this article that CAR activators do not appear to be strong inducers of Sults, especially in male mice, but are better inducers of Sults in female mice.…”
Section: Discussionmentioning
confidence: 53%
“…A gender difference in mouse hepatic CAR expression has been noted previously (Kawamoto et al, 2000;Ledda-Columbano et al, 2003). Furthermore, basal and inducible expression of Cyp2b10 mRNA in female liver is greater than that observed in males (Honkakoski et al, 1992;Ledda-Columbano et al, 2003).…”
Section: Xenobiotic Induction Of Car and Other Transcription Factorsmentioning
confidence: 62%
“…Due to limited availability of animals, most inducers were tested with either males or females. Induction of CAR-dependent gene expression by the differentially acting CAR agonists TCPOBOP and phenobarbital was studied with mice from both genders, because gender differences in response to CAR agonists have been reported in the literature (Ledda-Columbano et al, 2003). Livers were isolated, and hepatic levels and zonation of various mRNAs and proteins were analyzed.…”
Section: Resultsmentioning
confidence: 99%